Storytelling Therapy in schools: Supporting Emotional Well-Being through Narative Practices - Maulida Shanti Yusuf; Rania Khatib; Nasser Qudah (Yayasan Adra Karima Hubbi, 2025)
Background. Emotional well-being has emerged as a central concern in contemporary school contexts, as students increasingly encounter psychological, social, and academic pressures that affect learning and development. While schools have adopted various social-emotional learning initiatives, therapeutic approaches grounded in narrative meaning-making remain underutilized. Purpose. The primary aim of this study is to examine how storytelling therapy implemented in school settings supports students’ emotional well-being through narrative practices. Method. This research employed a qualitative descriptive design with a narrative-oriented approach. Participants included students and educators selected through purposive sampling in schools implementing storytelling-based activities. Results. Findings indicate that storytelling therapy enhances emotional expression, emotional regulation, peer interaction, and self-confidence among students. Sustained narrative participation fostered gradual emotional openness and strengthened social bonds within classrooms. Case-based analysis illustrated individual emotional transformation through symbolic storytelling and narrative reframing of personal challenges. Conclusion. The study concludes that storytelling therapy is an effective school-based approach for promoting emotional well-being through narrative meaning-making.